Upaya Memperbaiki Bersihan Jalan Nafas Pada Anak Dengan Ispa - Nurrohim, Alif; , Siti Arifah , S.Kp., M.Kes (2017)
Background: Acute respiratory infection (ARI) occurs in the throat, sinuses, air salura, or lungs. The cause of ARI due to a virus or bacteria. Viruses or bacteria are issued by people with respiratory tract infection through sneezing or when coughing. The main issues that need to be ditangai in children with acute respiratory infection with inhaled manually, because it can launch an increased secretion needs. Based on medical record showed that in one year the children suffering from ARI in 2016 reached 900 people. Objectives: The general objective of this scientific writing is to provide nursing care to improve airway clearance. The specific objective of this scientific writing is to analyze the assessment, diagnosis, planning, implementation and evaluation of children with ARI Methods: Descriptive study approach and perform nursing care in ARD patients by improving airway clearance which includes assessment, nursing diagnosis, planning, implementation, and evaluation. Results: After nursing actions during 3x visit to the action form, encourage the family to provide food inhalation manual and educating families about ISPA can terpenuhi. Conclusion: Nursing care in patients with airway clearance ISPA, the evaluation on day 3 results partly proved the problem is resolved with reduced secretion Keywords: ARI, Airway Clearance, Inhalation Manual